Efficacy of antibiotic selected on the basis of sensitivity of operation theatre microflora during orthopedic surgery in dogs - NANHAR, BALROOP SINGH; SHARMA, S N; BHADWAL, M S; SHARMA, D K (The Indian Journal of Animal Sciences, 2013)
Apparently healthy mongrel dogs (12) weighing between 12-20kg were randomly divided into 3 groups of 4 each. Routine aseptic procedures were adopted. Femur fracture, under general aneshthesia, was created with a wire saw. TheÂ  fracture was repalited by intramedullary pinning. No antibiotic was used in group 1, the experience based outinely used antibiotic (ampicillin) was administred in group 1 animals did not progress satisfactorily as evidenced by clinical signs, hematological results and culture examination. One animal died and in another pin was dislodged. The animals recovered after administering ampicillin. In group 2 the recovery was better as compared to group 1. The clinical signs were evident till sevents post operative day (POD) which could be correlated with haematology and clinical findings. In group 3, recovery was faster and uneventful than in other groups. All the parameters were within the normal range. The results confirm that operation theatre environment is the mst common source of surgical wound infection. The antibiotic selected on the basis of antibiotic sensitivity testing of the operation theatre enviroment proved more effective in controlling infection than the routinely used antibiotic.